Methodological Considerations for Possibilities to Integrate the Grounded Theory and Action Research - Žydžiūnaitė, Vilma (Pedagogika, 2016)
Today we find a variety of national and international scientific resources that describe different versions of Grounded theory (GT). It is referred to GT authors (Glaser, Strauss & Corbin, Charmaz) and other researchers who apply different versions of GT and write about its fundamental strengths: systematic procedures, emancipatory decisions, self-empowerment of researcher to immerse into the data, and emerging theory being substantiated by empirical data and its interpretation. Reading the resources leads GT researchers to the understanding of this methodology as a set of systematic procedures which are applied in an integrated way by striving to the fundamental outcome – created original and based on empirical data GT. Researchers constantly applying GT alone may learn its principles, progress of adopting the necessary intellectual skills though at some point experience “being trapped”. Why? Because GT application does not stimulate their creativity and this methodology becomes “well-known” routine or “typical” process by recognizing what is “right” and “wrong”. Such attitude regarding the qualitative research methodology is risky due to emerging normative approach to the range of qualitative data collection, analysis and interpretation. Initially, the researchers’ self- empowerment to manage the different GT versions helps to avoid the routine. However, in this case there comes a time when each version is assigned by researcher with “labels”. For example, Glaserian version is named classic, emerging and theory-driven; version of Strauss and Corbin is seen as hypothesis testing, though in fact it is treated as a resource of hypotheses; in Glaserian version GT emerges, and in Strauss and Corbin version GT is forced. Constructivist GT version states that various social realities are relevant, and the common establishment of knowledge is recognized as outcome of cooperation between researcher and research participants. However, is it possible to find the emerging and forced moments in all GT versions? This question is not easy to answer accurately. There are similarities between the mentioned GT versions, though their differences are more conceptual than procedural. When researcher exploits his/her potential of creativity by applying a range of GT versions, then the time may come to make a decision to integrate GT and other methodologies. Thus, researcher’s attempts to combine GT with other methodologies being close to the emerging nature and plural data resources methodology of GT are creditable and deserve encouragement. The article presents the example of such decision when combination or integration of GT and Action Research (AR) is considered. Research question: Do similar features of GT and AR allow combining these methodologies aiming at validity of results within the research process? Research aim is to argue the possibilities to integrate GT and AR. Methods. The information in the article is presented consequently: each methodology is presented individually and then possibilities for integration or combination are discussed. The overview for analysis of possibilities to integrate GT and AR was used in the study by providing arguments and generalization of considerations. Conclusions. Integration of GT and AR illustrates the responsibility of researcher in shaping the design of a specific research and solving specific research issue. Decision to integrate GT and AR allows researcher to be the expert in both methodologies and strictly respect the principles, procedures, and methods. Researcher may not fully apply two methodologies, starting a study with one while concluding it with another. Such a decision is risky, causing uncertainty and leading to unreliable findings. However, the integration of these methodologies cannot and should not be a mechanical action. Researcher must clearly determine the object of the research – is it process or change? This will result in a clear and basic methodology of choice, respectively GT or AR. Then, the study will be based on the fundamental principles and steps of the chosen methodology. And the relevant components will be chosen by researcher in data collection and/or analysis of process (-es). GT and AR integration is possible, therefore GT and AR complement each other and their combinations depend of researcher.